PENGEMBANGAN BUKU AJAR MATA KULIAH PENGEMBANGAN KURIKULUM IPS TERPADU TERINTEGRASI ISLAM - Yasri, Hayyun Lathifaty; Sari, Ulfi Andrian (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2019)
This study was done to answer a problem about the Islamic Curriculum Development leaning book wich still limited. So, this study aims to develop a Curriculum Development learning book with integrating the islamic values in it. This book was developed to be used as a reference book in the Curriculum Development Study in the Social Science Education Major, Faculty of Tarbiyah and Teacher Training, UIN Maulana Malik Ibrahim Malang. This study employed the development method by Dick Carey that was reduced in 5 steps, there are: 1) need analysis, 2) material analysis, 3) learning book writing process, 4) expert judgment and it trial, and 5) revision. The result of this study is the arrangment of the learning book of Curriculum Development Study that was integrated with islamic values. The book was contents by: 1) preface, 2) table of contents, 3) material descriptions, 4) the summary, 5) learning exercise, and the last 6) bibliography.Keywords: learning book; curriculum development; islamic integration.Â